Evaluation of Multi-hop Ad-hoc Routing Protocols in Wireless Seismic Data Acquisition - Makama, Aliyu; Kuladinithi, Koojana; Ahmed, Musab; Timm-Giel, Andreas (Electronic Communications of the EASST, 2021)
Due to impediments associated with cable-based seismic survey, Wireless Seismic Data Acquisition (WSDA) has recently gained much attention from contractors, exploration companies, and researchers to layout enabling wireless technology and architecture for Wireless Geophone Networks (WGN) in seismic explorations. A potential approach is to employ multi-hop wireless ad-hoc communication. In this study, we propose a multi-hop WGN architecture consisting of several subnetworks to realize the expected network performance. We investigate the performance of proactive and reactive routing protocols to examine the optimal number of geophones that could be effectively supported within a subnetwork. The performance metrics used are packet delivery ratio (PDR) and average end-to-end delay.